APPLICATION OF THE FLOTATION FOR THE EVALUATION OF THE LEACHING OF GOLD IN THE LEACHING CIRCUIT BY CYANIDATION (LACCEI, 2024)
Laboratory tests using sodium cyanide leaching and flotation techniques were performed to determine how to extract the most Gold from a sulphide ore with around 0.2% copper content. Since the sulfide ore was found in the transition zone between oxidized ore and sulfides, it was proposed to carry out flotation to recover the greatest amount of copper and thus obtain a tailing with a lower copper content that is below 0.1%. Two parallel tests were proposed to evaluate the extraction of gold in the cyanide leaching circuit, test 1 consists of carrying out a baseline leaching (mine mineral) and test 2 starts with flotation and tail (tailings) from flotation perform cyanide leaching. NaCN leaching tests were performed on the mineral, obtaining a final extraction of 74.52%. A serial test was also carried out that consisted of differential flotation to remove the copper present and then the remnant of the mineral was leached with NaCN, obtaining a total gold extraction of 84.37%.